Comparison of Biological Age Prediction Models Using Clinical Biomarkers Commonly Measured in Clinical Practice Settings: AI Techniques Vs. Traditional Statistical Methods - Bae, Chul-Young; Im, Yoori; Lee, Jonghoon; Park, Choong-Shik; Kim, Miyoung; Kwon, Hojeong; Kim, Boseon; Park, Hye ri; Lee, Chun-Koo; Kim, Inhee; Kim, JeongHoon (Frontiers in Analytical Science, 2021)
In this work, we used the health check-up data of more than 111,000 subjects for analysis, using only the data with all 35 variables entered. For the prediction of biological age, traditional statistical methods, and three AI techniques (RF, XGB, SVR, DNN), which are widely used recently, were simultaneously used to compare the predictive power. This study showed that AI models produced about 1.6 times stronger linear relationship on average than statistical models. In addition, the regression analysis on the predicted BA and CA revealed similar differences both in terms of the correlation coefficients((linear model: 0.831, polynomial model: 0.996, XGB model: 0.66, RF model: 0.927, SVR model: 0.787, DNN model: 0.998)) and R^2 values. Through this work, we confirmed that AI techniques such as the DNN model outperformed traditional statistical methods in predicting biological age.